Assessment of the Preservation and Conservation of Teachers’ Records at Rubanda District Local Government - Gumoshabe, Alexander R. (Kabale University, 2023)
The study assessed the preservation and conservation of teachers’ records at Rubanda Local Government in central registry. The study was guided by the following objectives: to identify the activities carried out in the preservation and conservation of teachers’ records at Rubanda district Local Government, to examine the causes of deterioration of teachers’ records at Rubanda district. Local Government, to assess the challenges faced in the preservation and conservation of teachers’ records at Rubanda district Local Government and to propose strategies to improve the preservation and conservation of teachers’ records at Rubanda district Local Government. Literature review focused on the specific objectives and was got through documentary analysis and internet sources. The population of Rubanda District Local Government office consisted of over 30 staff in different departments such as the registry department, finance department, community development, veterinary and animal husbandry, health department, administration and users (clients) such as teachers. Descriptive research design was used and a sample size of 17 respondents was used and these included 4 records staff (one records manager, two records assistants and one office messenger) and 10 teachers and 3 administrators. Data collection methods used included questionnaire method and interviewing method. Data was then analyzed using words and statements, and later presented in form of thesis and tables. The findings of the study also revealed that, Rubanda district Local Government has no means for the preservation and neither conservation of records. Records are stored in boxes, some placed on shelves, cabinets and on tables. The findings of the study revealed that, biological threats, mishandling of records, dust, humidity, fungi, pests and moulds, pollution, plucking of pages of documents and poor retrieval and filling practices are leading causes of deterioration of teachers records.